A study of suicidal thoughts and behaviour in a sample of adults affected by the 9/11 attacks on New York City's World Trade Center. (2nd January 2022) - Xue, Judy; Raitt, Josh; Roaten, Kimberly; North, Carol S.
Abstract: Previous research on suicide risk in relation to disasters has yielded varying findings, likely resulting at least in part from inconsistencies in definitions of disaster exposure and assessment of psychiatric disorders. This study examined suicidal thoughts and behaviour in a sample of 379 adults affected by the 9/11 attacks on New York City, using carefully-defined disaster exposure variables and assessing psychopathology with full diagnostic criteria, nearly 3 years after the disaster. Only 7% of the sample reported any postdisaster suicidal thoughts or behaviour, only 1% of which were new (incident) after the disaster, amounting to very little evidence of incident suicidal risk. The occurrence of a postdisaster psychiatric disorder in nearly one-half of the sample (45%) was significantly associated with postdisaster suicide risk (15% vs 1%). Disaster trauma exposure was not associated with postdisaster suicide risk. The findings of this study are not consistent with the disaster experience itself giving rise to suicide risk. Nonetheless, the postdisaster setting provides opportunities for education about and surveillance for suicide risk and other mental health concerns.